2003
DOI: 10.2214/ajr.181.4.1810997
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation in the Treatment of Small Hepatocellular Carcinomas: Comparison of the Radiofrequency Effect With and Without Chemoembolization

Abstract: The combination of radiofrequency ablation and transcatheter arterial chemoembolization using doxorubicin markedly increased the extent of induced coagulation compared with radiofrequency alone, despite a small number of patients and the preliminary nature of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 32 publications
0
50
1
2
Order By: Relevance
“…With the new strategy of PAA combined with RFA, the number of percutaneous punctures per HCC was reduced in group A to an average of 2.76 ± 1.12, which was significantly less than that in group B, 3.36 ± 1.60 (P = 0.001), thus injury to patients was reduced. Kitamoto et al [20] reported that the average duration between TACE and RFA was 18.2 d. In our study, RFA could be performed immediately after blocking of the major feeding artery with PAA, which could reduce hospital stay.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…With the new strategy of PAA combined with RFA, the number of percutaneous punctures per HCC was reduced in group A to an average of 2.76 ± 1.12, which was significantly less than that in group B, 3.36 ± 1.60 (P = 0.001), thus injury to patients was reduced. Kitamoto et al [20] reported that the average duration between TACE and RFA was 18.2 d. In our study, RFA could be performed immediately after blocking of the major feeding artery with PAA, which could reduce hospital stay.…”
Section: Discussionmentioning
confidence: 72%
“…With the new strategy of PAA combined with RFA, the number of percutaneous punctures per HCC was reduced in group A to an average of 2.76 ± 1.12, which was significantly less than that in group B, 3.36 ± 1.60 (P = 0.001), thus injury to patients was reduced. Kitamoto et al [20] reported that the average duration between TACE and RFA was 18.2 d. In our study, RFA could be performed immediately after blocking of the major feeding artery with PAA, which could reduce hospital stay.In group A, 13 (17.33%) patients had a small amount of bleeding during PAA, most of which was detected at the first puncture, where the RFA needle punctured the area where the feeding artery entered the tumor. We supposed that the bleeding might have been caused by damage of the feeding vessels and incomplete ablation.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In the case of RF ablation, these treatments include, in addition to liposome-encapsulated doxorubicin therapy, treatments with intravenous liposomal cisplatin ( 18 ), liposomal 5-fl uorouracil ( 18 ), arsenic trioxide ( 20 ), and hydralazine ( 24 ); intravenous and intratumoral Pluronic block copolymers ( 28 ); intratumoral ethanol ( 11,39 ) and unencapsulated doxorubicin ( 12 ); intraperitoneal arsenic trioxide ( 20 ); interstitially implanted 5-fl uorouracil-laden polymer rods ( 27 ); oral sorafenib ( 21 ); and transarterial chemoembolization ( 19,23 ). In human trials, the benefi ts of combined RF ablation-intratumoral ethanol therapy ( 30,40,41 ) and combined RF ablation-transarterial chemoembolization ( 15,22,25,29,31,42 ) have been shown. The synergistic effect of combined RF ablation-chemotherapy has been best established with intravenous liposomal doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the RFA technique could be further developed to improve the therapeutic effects of this treatment. To enhance the therapeutic effect of RFA, several treatment modalities have been applied in addition to local treatment [24][25][26][27][28][29] . As one of the optional combination therapies, we have developed a novel combination therapy of P-EI-RFA and showed that this combination therapy accurately enlarged the area of induced coagulated necrosis.…”
Section: Discussionmentioning
confidence: 99%